Too Far Gone: The Psychological Games of Cormac McCarthy’s All the Pretty Horses - Michael Wainwright (European Journal of American Studies)
This article uses Jacques Lacan’s reading of the Freudian fort-dagame to analyze that most American of cultural constructs, the cowboy, at the time of that figure’s fading from the American landscape: the immediate postwar years.  With John Grady Cole, the protagonist of All the Pretty Horses (1992), Cormac McCarthy provides a suitably situated subject for this critical endeavor, one whose subjective characteristics become present through dramatically playful division of his maternal imago.  These games of psychoanalytical maturation, which emerge from the alternation between psychoanalysis in theory and that theory in critical practice, and which trace their subject’s successive relocations to alternative sides of the American-Mexican border, articulate the inevitable though resisted diminishment of Cole’s cultural construction.